Henrietta Szold Hadassah and the Zionist dream - Klagsbrun, Francine (Jewish lives (New Haven, Conn.), 2024)
Award-winning author Francine Klagsbrun reveals the complex life and work of Henrietta Szold, founder of Hadassah and a Zionist trailblazer Henrietta Szold (1860-1945) is renowned as the founder of Hadassah, the Women's Zionist Organization of America, which quickly became one of the most successful of all Zionist groups. In her work with Hadassah, Szold used a combined ethical and pragmatic approach aimed at improving the lives of both Jews and Arabs. She later moved to Mandate Palestine to help shape education, health, and social services there. The pinnacle of her career came in her seventies, when she took on the task of directing the Youth Aliyah program, which rescued thousands of young people from the Nazis and resettled them in Palestine. Using Szold's copious letters, diaries, and essays, along with other archival documents, Francine Klagsbrun traces Szold's life and legacy with an eye to uncovering the person behind the Zionist icon. She reveals Szold as a complex human being who had to cope with controversy and criticism, a workaholic with an outsized sense of duty, and an idealist who fought for her beliefs even as she questioned her own abilities. With deep insight, Klagsbrun introduces readers to this extraordinary woman, whose impact on women's lives as well as on education and health systems still resonates.